Manajemen Mutu Dalam Peningkatan Kompetensi Profesional Guru Di MAN 2 Model Medan - Riduan Pohan, Muhammad Rizki (Journal of Education and Teaching Learning, 2021)
Quality management, and find efforts in improving teacher professional competence in MAN 2 Model Medan. This type of research i s a qualitative descriptive study that is a research procedure that produces descriptive data in the form of written or oral words from people and actors observed, directed from an individual's background as a whole (holistically) without isolating the individual and his organization in a variable but looking at it as part of a wholeness. This study uses qualitative techniques in data collecting. In general, in qualitative research, researcher uses data collection techniques through interviews, observations, and document studies. The results showed: (1) That the MAN 2 Model Medan Madrasa teacher was a professional teacher. Teacher professionalism correlates with the quality of educational products. Professional teachers make education or a quality learning process, so students are happy to participate in the learning process, so that human resources are produced from quality madrasa graduates, (2) Generally the teachers at MAN 2 Model Medan apply various models of learning both learning cooperative and technology-based learning, (3) That there are two learning strategies that are always carried out by teachers in implementing the learning and teaching process, namely cooperative learning and technology-based learning, the number of teachers in MAN 2 Model Medan have been certified and have better career paths. This can be seen from the large number of teachers who have undertaken higher education, namely Masters. improve the quality management function in the madrasa in its leadership, the processes of the quality management function are carried out, namely: Planning, organizing, Scavenging, and monitoring.